The Teaching of Sciences for the initial years of Elementary School: the experimentation as a didactic possibility (Research, Society and Development, 2019)
Discussing the use of a methodology that can assist in the teaching of Science, especially in the initial grades of Elementary School, considering the current educational and social context in which we find ourselves, becomes a prominent issue to be debated. In this scenario of pedagogical tradition, the activities of investigative experiments appear as a didactic possibility for teaching science, considering this methodology as a means and not an end to solve such problems. In this sense, the present work sought to investigate the conception of experimentation according to the perception of five teachers of Sciences of the initial years of Elementary Education of a public school in Castanhal-PA. To this end, we are pursuing the paths of a qualitative research, with information organized from semi-structured questions in the form of an interview. Thus, we present different conceptions about experimentation as a didactic possibility for teaching science, considering the pedagogical content of the use of this methodology in its classroom practices, as well as the main difficulties encountered by teachers who decide to use experimentation in their science classes. It is necessary that teacher training courses discuss with future teachers the need to re-signify experimental work, no longer as a recipe of cake to be followed, but as a possibility to be an instrument for solving a real problem.